ZnO nanofiber (NFs) growth from ZnO nanowires (NWs) by controlling growth temperature on flexible Teflon substrate by CBD technique for UV photodetector. (December 2016) - Farhat, O.F.; Halim, M.M.; Ahmed, Naser M.; Qaeed, M.A.
Abstract: In this study, ZnO nanofibers (ZnO NFs) were successfully grown for the first time on Teflon substrates using CBD technique. The well-aligned ZnO nanorods (ZnO NRs) were transformed to ZnO nanofibers (NFs) by varying growth temperature and growth time. The high intensity and distinct growth orientation of peaks observed in the XRD spectra of the NFs indicate high crystal quality. The field emission scanning electron microscopy (FESEM) revealed high density of small diameter sized and long ZnO nanofibers (NFs) that are distributed in random directions. Raman analyses revealed a high E2 (high) peak at 436 nm, which indicates the wurtzite structure of ZnO. A flexible ZnO nanofiber (NFs)-based metal-semiconductor-metal UV detector was fabricated and analyzed for photo response and sensitivity under low power illumination (375 nm, 1.5 mW/cm 2 ). The results showed a sensitivity of 4045% which can be considered a relatively high response and baseline recovery for UV detection. Graphical abstract: Highlights: Synthesis ZnO Nanofibers (NFs) by CBD. ZnO Nanofibers (NFs) deposited on flexible Teflon substrate. Control of growth temperature and transformation of ZnO nanorods (NRs) to ZnO nanofibers (NFs).